Fusarium verticillioides and its fumonisin production potential in maize meal - das Chagas Cardoso Filho, Francisco (2015)
This study aimed to identify the presence of fungi of the genus Fusarium and to evaluate the presence of contamination of fumonisin in maize meal destined to human consumption in the city of Teresina, Piauí, Brazil. It was used 30 samples of maize meal of six different brands sold in supermarkets. Mycological evaluation was carried out immediately. Then aliquots were stored at - 4 °C for later analysis of fumonisins. It was obtained 34 isolates from Fusarium verticilloides. These isolates had the ability to produce fumonisins B1, B2 and B3, with values ranging from 48.2 to 1190.1 μg g-1 for B1; from 6.7 to 311.5 μg g-1 for B2; and from 23 to 667 μg g-1 for B3. The fumonisin concentrations for isolates ranged from 84.3 to 2168.6 μg g-1. All the samples presented fumonisins with values ranging from 0.10 to 2.13 μg g-1. Isolates from strains of F. verticillioides were obtained in the maize meal samples, and the lots examined had different levels of fumonisins, which may represent risks to consumers.